1999
DOI: 10.1080/02615479911220051
|View full text |Cite
|
Sign up to set email alerts
|

A group supervision model for broadening multiple-method skills of social work students

Abstract: This article describes a comparative model of group supervision of social work students in their second and third years in the Undergraduate Social Work Programme at the University ofHaifa School of Social Work. The model is designed with the purpose of offering group supervision to all students in the programme and takes into account the complexity of multicultural students. Under this model, second-year students receive group guidance in their individual casework in the field; third-year students are guided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The present research recognizes the vast influence of commitment to the profession on training processes and work outcomes (Arkin et al., 1999). Although the main objective of social work schools is to train students to deal with the profession properly and professionally (Freund, 2005; Lafleur, 2007), almost no studies were found dealing with students’ commitment to the profession.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The present research recognizes the vast influence of commitment to the profession on training processes and work outcomes (Arkin et al., 1999). Although the main objective of social work schools is to train students to deal with the profession properly and professionally (Freund, 2005; Lafleur, 2007), almost no studies were found dealing with students’ commitment to the profession.…”
Section: Introductionmentioning
confidence: 96%
“…In an era when social work schools assimilate new reforms and strategies aimed at adjusting themselves to new challenges and environmental changes, it is evident that students’ commitment to the profession is imperative, in addition to the acquisition of professional knowledge, skills and values (Loewenberg & Balalty, 1989). Supposedly, high commitment to the profession is a precondition for an eagerness to cope with the complex tasks currently demanded from social workers (Arkin, Freund, & Saltman, 1999). The article discusses social work students’ perceptions of training processes.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, despite its promise as a model that lends itself well to reflection and enhanced critical thinking, it has received more limited attention when compared with one-to-one supervision. Where it has received attention, the overwhelming emphasis has been on the learning potential that group supervision models afford to social work students rather than qualified practitioners (Alschuler et al, 2015;Arkin et al 2007;Bogo et al, 2004;Geller, 1995;Walter and Young, 1999;Wilbur et al, 1991) with the exception of a study of qualified practitioners conducted by Lietz (2008).…”
Section: What Is Group Supervision?mentioning
confidence: 99%
“…While there is a small body of literature on group supervision that identifies its potential for practice learning for social work students (Alschuler et al, 2015;Arkin et al 2007;Bogo et al, 2004;Geller, 1995;Walter and Young, 1999;Wilbur et al, 1991), group supervision has received less attention within the literature on child protection social work (Leitz, 2008). Furthermore, it has continued to be a subcategory that is devoid of study that seeks to understand and evaluate what happens within supervisory sessions in terms of theoretical frameworks relevant to the mode of group supervision being investigated (Carpenter et al, 2013a;Wilkins et al 2016).…”
Section: Non-judgmental Practicementioning
confidence: 99%
“…The application of the strengths perspective to supervision need not be limited to individual supervision. Recent descriptions of innovations in group supervision, whether expressly designed to promote strengths-based social work processes (Rapp, 1998) or only touching indirectly on issues related to the strengths perspective (Arkin, Freund, & Saltman, 1999), underline the potential of group supervision and peer-group supervision for facilitating the identification and development of therapeutic strengths by students and professionals engaged in strengths-based helping.…”
Section: Problem-based Assessments Encourage Individualistic Rather Than Social-environmental Explanations Of Human Problems Although It mentioning
confidence: 99%